Composite Materials and Advanced Materials Research. - Kim, Jong Hak; Lau, Alan K. T. (Scientific Books Collection., 2022)
Selected peer-reviewed extended papers abstracts of which were presented at the 7th International Conference on Composite Materials and Material Engineering (ICCMME), and the 12th International Conference on Advanced Materials Research (ICAMR) Aggregated Book.